International Colloquium with Strategic Partners: Advancing Teaching Excellence and Research in Pharmacy and Health Science / Suraya Sulaiman … [et al.] - Sulaiman, Suraya; Wong, Yuet Yen; Mokhtar, Nur 'Ainun; Che Lamin, Roz Azinur; Mat Daud, Siti Shahirah (UiTM Global @ Office of International Affairs, 2024)
In today's interconnected world, the pursuit of academic excellence must transcend geographical boundaries. Nowhere is this ethos more evident than in the field of pharmacy and health sciences, where collaboration, innovation, and shared commitment are essential in advancing knowledge, addressing global health challenges, and driving positive changes in human lives. The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Bertam Campus, Pulau Pinang, was honoured to host the "International Colloquium with Strategic Partners: A Focus on Teaching Excellence and Research in Pharmacy and Health Science". This international colloquium successfully served as a platform for knowledge exchange and the establishment of research collaboration.